In pursuit of ancient Cyrenaica... : two hundred years of exploration set against the history of archaeology in Europe (1706-1911) - Rekowska-Ruszkowska, Monika (Archaeopress, 2016)
This work examines travellers' accounts of their journeys to Cyrenaica, focusing in the main on an analysis of these accounts within the context of their significance to topographic surveys of the region.